2017
DOI: 10.1093/heapol/czx010
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators for institutional delivery among poor Mesoamerican women: a cross-sectional study

Abstract: Professional skilled care has shown to be one of the most promising strategies to reduce maternal mortality, and in-facility deliveries are a cost-effective way to ensure safe births. Countries in Mesoamerica have emphasized in-facility delivery care by professionally skilled attendants, but access to good-quality delivery care is still lacking for many women. We examined the characteristics of women who had a delivery in a health facility and determinants of the decision to bypass a closer facility and travel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…This result might indicate the low quality of care at the health clinics, which should be improved. Our findings are mostly consistent with findings from previous studies [8][9][10][11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 93%
“…This result might indicate the low quality of care at the health clinics, which should be improved. Our findings are mostly consistent with findings from previous studies [8][9][10][11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 93%
“…To corroborate these findings, one previous study reported poor quality of services as detrimental to health facility deliveries, particularly in the realm of ‘process’ i.e. standards of care employed in the provision of these services [ 37 , 38 ]. However, in the current study we were limited by the data availability and accordingly not in a position to comment on which indicators of quality were compromised.…”
Section: Discussionmentioning
confidence: 82%
“…Similarly, a study among Mesoamerican women revealed that there was a relationship between well-equipped health facilities and use of such facilities for delivery services. Thus, it was observed that women make long journeys to those facilities that were considered equipped [ 25 ]. This makes it imperative that good attention should be given to primary health centers and rural areas if the maternal death burden in Nigeria should be improved.…”
Section: Discussionmentioning
confidence: 99%